The impact of risk retention on the pricing of securitizations - Martin Hibbeln; Werner Osterkamp (Review of Derivatives Research, 2025)
Loan screening and monitoring are critical to loan performance, but incentives are diminished for securitized loans. Risk retention is intended to harmonize the interests of originators and investors; however, it is unclear to what extent investors anticipate and respond to originators' screening and monitoring incentives, particularly with respect to different types of risk retention. The theoretical literature suggests that equity retention is optimal in terms of screening efforts; thus, if investors anticipate these incentives, equity retention should lead to low credit spreads. Employing OLS and instrumental variables regressions, we empirically examine the effect of retention on spreads. Our analysis, based on a unique dataset of securitizations, reveals that the effects highly depend on the considered investment type. Credit spreads decrease by approx. 26 to 39 bps if the originator retains a material fraction of at least 5% of the deal's nominal value. For tranches with high information sensitivity—where screening and monitoring incentives are most critical—investors, though, impose an additional risk premium of 120 basis points when originators fail to retain a substantial portion of the securitizations. In addition, we find that transactions with vertical slice retention are associated with a notably higher risk premium than those with equity retention, demonstrating the differential impact of retention structures on investor perceptions. Overall, our results underline that the extent of asymmetric information, particularly with respect to different types of investments and risk retention, is an important component in the pricing of securitizations.
Keywords: D82; G01; G21; G24; 330; Security design; Asset-backed securities; Retention; Credit spreads